Comparing three models to explain precautionary online behavioural intentions. (12th June 2017) - Jansen, Jurjen; van Schaik, Paul
Abstract : Purpose: The purpose of this paper is to compare three social cognitive models in their ability to explain intentions of precautionary online behaviour. The models are: protection motivation theory (PMT), the reasoned action approach (RAA) and an integrated model comprising variables of these models. Design/methodology/approach: Data were collected from 1, 200 Dutch users of online banking by means of an online survey and analysed using partial least squares path modelling method. Findings: The two models equally explain about much of the variance in precautionary online behaviour; in the integrated model, the significant predictors of the two models remained significant. Precautionary online behaviour is largely driven by response efficacy, attitude towards behaviour and self-efficacy. Research limitations/implications: One limitation is that the predictor variables – "self-efficacy" and "attitude" – are represented by one item only in the path-analysis because of high cross-loadings of the other items with the dependent variable. Practical implications: The results give practitioners a potentially wider range of options to design preventative measures. Originality/value: The three models are successfully applied to online banking. This paper concludes that both PMT and RAA make a unique contribution in explaining variance for precautionary online behaviour. This paper is a re-publication of a previous conference paper (Jansen and van Schaik, 2016).